Novel Actinomycete Isolated from Bulking Industrial Sludge - White, Johanna M. (1986)
A novel actinomycete was the predominant filamentous microorganism in bulking activated sludge in a bench-scale reactor treating coke plant wastewater. The bacterium was isolated and identified as an actinomycete that is biochemically and morphologically similar to Amycolatopsis orientalis; however, a lack of DNA homology excludes true relatedness. At present, the isolate (NRRL B 16216) cannot be assigned to the recognized taxa of actinomycetes.